Quality of Life in Children with Epilepsy in Private and Public Tertiary Care Centers in India - Karnavat, Purva Keni; Hegde, Anaita Udwadia; Kulkarni, Shilpa (International Journal of Epilepsy, 2018)
Background Pediatric epilepsy is associated with various comorbidities. It is known that children with epilepsy have a compromised health-related quality of life (QOL) and may be affected across physical, psychological, social, and educational domains.Aims and Objectives (1) To study QOL in children with epilepsy from private and public outpatient departments, (2) study various risk factors affecting QOL, and (3) compare risk factors between groups.Methods Sample consisted of 400 and 201 children aged 5 to 18 years from private and public settings with epilepsy taking antiepileptic drugs (AEDs) for at least 6 months. Structured case record form was used to collect data on sociodemographic, clinical, and treatment parameters. QOL was measured by the Pediatric Quality of Life Inventory (PedsQL) questionnaire (in the local language). Adverse effects were monitored by Pediatric Epilepsy Side Effects Questionnaire (PESQ). Univariate regression analysis was performed on the data (p < 0.005).Results Overall PedsQL score was 67.21 ± 29.391 and 78.66 ± 9.161 in private and public settings, respectively (p = 0.000). QOL was affected significantly by age of the child, educational and economic background of the caregivers, age at the onset of epilepsy, seizure frequency, duration of treatment, number of drugs, presence of comorbidities, intelligence quotient (IQ) levels of children, and PESQ score in both the groups. Total PESQ score was 18.63 ± 17.02 and 7.69 ± 10.646 in private and public settings, respectively (p = 0.000).Conclusions Children with epilepsy have a compromised QOL. Risk factors relating to QOL are numerous. Educational and economic status of caregivers plays a significant role in awareness of the problem.
Keywords: quality of life; adverse effects; pediatric epilepsy; private and public tertiary care centers